Analisis Kesulitan Membaca Permulaan Siswa Kelas Rendah di SUN Bimbel Batangtoru - Dwi Utami Panggabean; Tuti Alawiyah Matondang; Dedek Oktavia Nasution; Rama Nida Siregar (STKIP Subang, 2026)
Early reading ability is a fundamental foundation for the academic success of elementary school students. However, in reality, many lower-grade students still experience difficulties in this area. This issue is an important concern, especially in tutoring institutions that support formal education. This study aims to analyze the forms and factors causing early reading difficulties among lower-grade students at SUN Bimbel Batangtoru. This research uses a qualitative approach with a descriptive method. The research subjects are lower-grade students who experience reading difficulties, with data collection techniques including observation, interviews, and documentation. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that early reading difficulties include difficulty in recognizing letters, distinguishing letter sounds, reading syllables, and combining words into simple sentences. The factors causing these difficulties consist of internal factors, such as low learning interest and students' cognitive abilities, as well as external factors, such as lack of family support and less varied teaching methods. These findings show that reading difficulties are not only caused by individual abilities but are also influenced by the learning environment. The conclusion of this study emphasizes the importance of using appropriate teaching methods and parental support in improving students' early reading skills. The implication of this study is the need to develop innovative and interactive learning strategies, as well as collaboration between teachers and parents to overcome reading difficulties in lower-grade students.